Association between circadian syndrome and chronic diarrhea: a cross-sectional study of NHANES 2005–2010 data - Ding, Liang; Duan, Jinnan; Yang, Tao; Jin, Chaoqiong; Lv, Shanmei; Ma, Ahuo; Qin, Yuehua (Frontiers in Physiology, 2024)
Background: Circadian rhythms are reported to influence physiological processes in the gastrointestinal system, but associations between circadian syndrome (Circs) and chronic diarrhea (CD) remain unclear. Here, we explored such relationships to provide new insights on CD management. Methods: We conducted a cross-sectional retrospective analysis using National Health and Nutrition Examination Survey (NHANES) data between 2005 and 2010. Univariate and multivariable logistic regression analyses were performed on weighted data to explore associations between Circs and CD. Results: Results were presented using forest plots, odds ratios (OR), and 95% confidence intervals (CI). Data with P < 0.05 values were considered statistically significant. In total, 5661 US participants, of which 412 had CD (weighted percentage = 6.20%), were finally enrolled. In univariate logistic regression analyses, participants with Circs had a significantly higher risk of CD (OR = 1.51, 95% CI: 1.15–1.99). After adjusting for covariates, Model 2 (OR = 1.40, 95 CI%: 1.03–1.90) and Model 3 (OR = 1.42, 95 CI%: 1.01–2.00) data were consistent with Model 1 data. Additionally, the number of Circs components was positively associated with CD in all three models. Subgroup analyses revealed an association between CD and Circs occurred in participants who had high blood pressure (OR = 2.46 95 CI%: 1.48–4.11, P < 0.001). Conclusions: In this cross-sectional study, we found that Circs is positively associated with the risk of CD in US adults, especially in those with high blood pressure. This association may provide new management strategies for CD.